Using CaCO3 and Kalamansi Squash to Improve Texture and Flavor Marning Kalamansi Orange Corn - Mediansyah, Berji Cikdwi; Moulina, Methatias ayu; Prasetya, Andwini; A, Darius (SINTA Journal (Science, Technology, and Agricultural), 2025)
Corn is one of the crops widely planted by farmers in Indonesia, because corn is the second source of carbohydrates as a staple crop to replace rice (Permatasari, 2013). Corn is very popular because of its delicious taste. In addition to its delicious taste, corn also contains many nutrients, such as fiber, protein, carbohydrates, minerals and vitamins. The processing of Kalamansi orange corn marning products using CaCO3 was carried out, in order to improve the texture and to utilize the typical orange fruit of Bengkulu. As well as being able to make Kalamansi orange corn marning crispy and as a snack that is loved by all groups. This study consisted of 2 treatments, the first treatment using calcium carbonate (CaCO3) consisting of 3 levels, namely: 1%, 3%, 5% and the second treatment using the addition of Kalamansi squash consisting of 2 levels, namely: 25% and 50% so that it becomes 6 treatments. Indicates that the high concentration of Kalamansi squash combined with the addition of CaCO3 in small amounts can increase the high yield of marning. The yield ranges from 78.87% to 91.03%. Water content is 6.57%, fiber content is 1.66%, carbohydrate content is 21.12%, texture content is 1411.3002%, and vitamin C is 0.43%. The organoleptic test results produced have the highest values in color 3.55 (like), aroma 3.15 (somewhat like), texture 3.20 (somewhat like), and taste 3.55 (like). The largest profit obtained from this treatment is Rp. 5,306,064 with a monthly income of Rp. 8,672,064.